2021
DOI: 10.1021/jacs.1c07975
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Dynamics and Roles of Iron Incorporation in Nickel Hydroxide Water Oxidation Catalysts

Abstract: The surface of an electrocatalyst undergoes dynamic chemical and structural transformations under electrochemical operating conditions. There is a dynamic exchange of metal cations between the electrocatalyst and electrolyte. Understanding how iron in the electrolyte gets incorporated in the nickel hydroxide electrocatalyst is critical for pinpointing the roles of Fe during water oxidation. Here, we report that iron incorporation and oxygen evolution reaction (OER) are highly coupled, especially at high workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 53 publications
3
86
1
1
Order By: Relevance
“…These in situ formed oxyhydroxides could also serve as active sites and improve the OER activity of the catalyst. [15,57] Moreover, the decrease of the Se content in the catalyst indicates the leaching of the Se species from the catalyst into the electrolyte where it may oxidize to SeO 3 2− ions. Due to its good adsorption ability, the SeO 3 2− ions may be adsorbed back to the surface of the catalyst during the OER catalysis, where it could promote the adsorption of the intermediates.…”
Section: Resultsmentioning
confidence: 99%
“…These in situ formed oxyhydroxides could also serve as active sites and improve the OER activity of the catalyst. [15,57] Moreover, the decrease of the Se content in the catalyst indicates the leaching of the Se species from the catalyst into the electrolyte where it may oxidize to SeO 3 2− ions. Due to its good adsorption ability, the SeO 3 2− ions may be adsorbed back to the surface of the catalyst during the OER catalysis, where it could promote the adsorption of the intermediates.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we further tested the electrocatalytic hydrogen evolution reaction (HER) performance of monadic and binary metal hydroxides, and their performance is shown in Figures S1 and S2 . It can be seen that 3D transition metal base hydroxides, such as Ni, Co, and Fe, have quite high activity, since Fe 3+ can broaden the interlaminar space of 2D materials and enhance their mass transfer behavior [ 54 ]. Meanwhile, the synergistic effect between Fe and the LDH lamellar structure can shorten the ion transport distance at the nanometer scale, so that Fe-doping can further improve its catalytic performance.…”
Section: Resultsmentioning
confidence: 99%
“…The NiOxHy layer derived from the NiSe precatalyst layer can have porous morphology with more defect/edge sites that are favorable for Fe incorporation in comparison with the NiOxHy layer derived from a Ni foil substrate. 3,59,[61][62][63][64] Also, it was observed that the Fe composition of 100-NiSe/Ni-CV was higher than that of 100-NiSe/Ni-CP as the Fe composition of Ni-CV was higher than that of Ni-CP. This finding again confirms that CV with both anodic and cathodic potential sweeps is more favorable for Fe incorporation than CP with only anodic potential applied.…”
Section: Study Of Cp and CV Characteristics For Nise Precatalysts On ...mentioning
confidence: 99%